2021
DOI: 10.1021/jacs.1c09222
|View full text |Cite
|
Sign up to set email alerts
|

London Dispersion Helps Refine Steric A-Values: Dispersion Energy Donor Scales

Abstract: We suggest a scale of dispersion energy donors (DEDs) that allows for direct comparisons with steric effects. This scale is based on the classic A-values and allows groups to reorient to minimize strain, thereby providing an advantage over raw group polarizabilities. The A-value can no longer be considered purely a steric factor. Even for groups that do not participate in charge transfer or electrostatic interactions, the A-value includes Pauli repulsion (steric hindrance) and attractive London dispersion (LD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 89 publications
0
43
0
Order By: Relevance
“…For example, the dispersive stabilization from bulky aryl and alkyl substituents has been found to be key in enabling the isolation of very reactive organometallic compounds and predicting reactivity. 11,[13][14][15][16][17][18][19] Similar studies have also been under- taken for carbene and phosphine ligands. [20][21][22][23] By comparison, few investigations have systematically and explicitly considered dispersive bond stabilization in complexes featuring bulky amide ligands, despite the prevalence of these ligands in coordination chemistry.…”
Section: Introductionmentioning
confidence: 74%
“…For example, the dispersive stabilization from bulky aryl and alkyl substituents has been found to be key in enabling the isolation of very reactive organometallic compounds and predicting reactivity. 11,[13][14][15][16][17][18][19] Similar studies have also been under- taken for carbene and phosphine ligands. [20][21][22][23] By comparison, few investigations have systematically and explicitly considered dispersive bond stabilization in complexes featuring bulky amide ligands, despite the prevalence of these ligands in coordination chemistry.…”
Section: Introductionmentioning
confidence: 74%
“…Considering the steric size of commonly utilized silyl groups, it is reasonable to hypothesize about the potential of these groups to serve as DEDs because they are far more polarizable. 43 with silyl groups directly attached in the 1,4-/1,6-position, and we demonstrated that an increase in size from TMS to extremely bulky tris(trimethylsilyl)silyl (TTMSS) leads to destabilizing internal strain on the COT backbone dominating the equilibrium between 1,4-and 1,6-COT. 44 The extended COT system under consideration here circumvents this problem.…”
Section: ■ Introductionmentioning
confidence: 84%
“…This molecular balance consists of two distinct valence isomers (Scheme ) that can equilibrate via a double-bond valence bond isomerization. , For bulky tert -butyl substituents, experimental ,,, and computational , studies suggest the “folded” 1,6-isomer to be preferred in solution and in the gas phase. Considering the steric size of commonly utilized silyl groups, it is reasonable to hypothesize about the potential of these groups to serve as DEDs because they are far more polarizable . In a recent study, we have addressed the effective size of commonly used silyl groups by utilizing a disubstituted COT molecular balance with silyl groups directly attached in the 1,4-/1,6-position, and we demonstrated that an increase in size from TMS to extremely bulky tris­(trimethylsilyl)­silyl (TTMSS) leads to destabilizing internal strain on the COT backbone dominating the equilibrium between 1,4- and 1,6-COT .…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined total of multiple LD‐interactions in larger molecules can generate significant stabilization of the order of tens of kcal mol −1 . The importance of these effects has been highlighted in several studies, aided by more efficient computational methods [4a,b] …”
Section: Methodsmentioning
confidence: 99%